The relevance of gunshot residues in forensic science. Issue 1 (23rd August 2022) - Minzière, Virginie Redouté; Gassner, Anne‐Laure; Gallidabino, Matteo; Roux, Claude; Weyermann, Céline
Abstract: Gunshot residues (GSR) are routinely exploited by forensic scientists in the investigation of firearm‐related events. While many new techniques are daily reported in the literature for the analysis of GSR, there is still a significant lack of data on the transfer, persistence, and prevalence of GSR. Such fundamental knowledge is essential to fully exploit the information potential of GSR for investigation or in Court. This article provides an overview of the relevant questions related to GSR, more particularly to infer about the trace's origin (i.e., is it from a firearm discharge?) and the activity that caused transfer (e.g., primary, secondary, or subsequent transfer). GSR production and composition will be briefly described, considering both inorganic and organic components. Then, the available knowledge about the primary transfer, the secondary transfer, and the persistence of GSR will be outlined, as well as the prevalence (background level) of the targeted elements and/or compounds in the environment, more particularly on the hands of people unrelated to firearm incidents. Finally, the methods developed for the collection, analysis, and interpretation of GSR will be discussed. A holistic approach combining fundamental forensic science knowledge about GSR transfer, persistence, and prevalence together with other available information is discussed as a path forward to increase the relevance and value of the GSR trace in practice. This article is categorized under: Crime Scene Investigation > From Traces to Intelligence and Evidence Forensic Chemistry and Trace Evidence > Trace Evidence Forensic Chemistry and Trace Evidence > Explosive Analysis Abstract : Gunshot residue is a relevant trace in the investigation of firearm related events. While much research has been carried out to develop detection and analysis methods, the focus needs now to shift from means to purposes. More knowledge on the trace characteristics, how it transfers, persists and the prevalence in the environment, will lead to a more reliable evaluation from a forensic rather than analytical perspective.